2008
DOI: 10.2174/1874453200801010048
|View full text |Cite
|
Sign up to set email alerts
|

Size and Composition of Foraging Flights in Two Species of Piscivorous Colonial Birds: Limited Evidence for Intra- or Interspecific Information Transfer

Abstract: Colonial birds must derive benefits from living in conspecific groups and with other species. One possible benefit is that they follow previously successful individuals to foraging sites (information center hypothesis). To test for evidence of intra-and interspecific information transfer, we assessed the group size and composition of flights of doublecrested cormorants (Phalacrocorax auritus) and American white pelicans (Pelecanus erythrorhynchos) at two mixed colonies. Flights by solo individuals were the mos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…On Last Mountain Lake, depth and aquatic habitat variation along the length of the lake likely influenced where birds foraged to some degree. Both cormorants and pelicans generally forage in shallow water, and will move to follow ephemeral sources of prey [33]. In addition, cormorants and pelicans breed at the north end of Last Mountain Lake [19], placing breeding colonies approximately 60 km from highly developed recreational areas at the southern end of the lake.…”
Section: Discussionmentioning
confidence: 99%
“…On Last Mountain Lake, depth and aquatic habitat variation along the length of the lake likely influenced where birds foraged to some degree. Both cormorants and pelicans generally forage in shallow water, and will move to follow ephemeral sources of prey [33]. In addition, cormorants and pelicans breed at the north end of Last Mountain Lake [19], placing breeding colonies approximately 60 km from highly developed recreational areas at the southern end of the lake.…”
Section: Discussionmentioning
confidence: 99%
“…However, we also found a substantial number of pelicans in off shore pelagic areas, particularly in large foraging flocks (> 100 birds). Previous studies [13,16] have identified littoral zones and shallow bays as critical foraging habitats for pelicans, although deeper water sites were also used, as observed in our study. Pelicans have also been observed co-foraging in deeper water with Double Crested Cormorants (Phalacrocorax auritus), and it has been proposed that they might benefit from cormorants flushing prey towards the surface, allowing pelicans to sometimes forage successfully in pelagic zones [17].…”
Section: Habitat Characteristicsmentioning
confidence: 66%